Pulmonary Function after Weight Loss in Obese Women Undergoing Roux-en-Y Gastric Bypass: One-Year Followup - Barbalho-Moulim, Marcela Cangussu (Hindawi Publishing Corporation, 2013)
Introduction. Obesity is a condition that causes damage to the respiratory function. However, studies have demonstrated that weight loss due to bariatric surgery has resulted in a huge improvement on some lung volumes, but controversy still persists regarding the behavior of the respiratory muscle strength and IRV (inspiratory reserve volume). Objective. To evaluate the effect of weight loss, after 1 year of the Roux-en-Y gastric bypass surgery (RYGB), on the lung volumes and the respiratory muscle strength in obese women. Methods. 24 obese women candidates were recruited for RYGB. Lung volumes (spirometry) and respiratory muscle strength were evaluated in preoperative period and one year after surgery. Results. There was a significant increase in some lung volumes. However, when examining the components of the VC (vital capacity) separately, an increase in ERV (expiratory reserve volume) and reduction of IRV were observed. Moreover, a statistically significant reduction in the values of respiratory muscle strength was recorded: MIP (maximal inspiratory pressure) and MEP (maximal expiratory pressure). Conclusion. Weight loss induced by bariatric surgery provides an increase in some lung volumes of obese women, but reduction in IRV. Additionally, there was also a reduction in the respiratory muscle strength.